The influence of the deep subtropical reservoir on the karstic riverine carbon cycle and its regulatory factors: Insights from the seasonal and hydrological changes. (1st November 2022) - Yi, Yuanbi; Li, Si-Liang; Zhong, Jun; Wang, Wanfa; Chen, Sainan; Bao, Hongyan; He, Ding
Highlights: Evaluating the carbon transformation intensity and amounts in the reservoir. The ultimate reservoir impacts consume river carbon in most of the seasons. Evaluating the influence of hydrological management and seasonal variation. Providing the scientific basis for weakening the influence of reservoir impacts. Abstract: Reservoirs are widely established worldwide with considerable environmental impacts, especially on the riverine carbon cycle. However, the influence of reservoirs on the cycling of different forms of carbon and its regulation factors (e.g., seasonal variations versus hydrological management) have not been simultaneously studied. To fill this knowledge gap, seasonal water samples from the deep subtropical reservoir (Longtan reservoir) in the Pearl River were collected, and the concentrations and stable carbon isotopes of dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), and particulate organic carbon (POC) were determined. The variations in stable carbon isotopes of DIC (-11.4‰ to -5.2‰), DOC (-32.2‰ to -26.2‰), and POC (-38.9‰ to -25.3‰) in the river-reservoir system indicated active production and degradation processes in different layers. We estimated that up to 23.0% of DIC, 20.5% of DOC, and most POC were intercepted or degraded within the reservoir. Our results further illustrated that hydrological management (water storage regulation) and seasonal variations from different perspectives controlled the cycling of different forms of carbon in the reservoir. In addition, with the gradual increase in the number of reservoirs, hydrological management can be considered as a potentially effective strategy to adjust the carbon biogeochemical cycling of reservoirs in the future. Graphical abstract: Image, graphical abstract